Co-combustion kinetics characteristics of semi-coke and bituminous coal under a drop tube furnace. Issue 1 (February 2021) - Guan, Jingyu; Yu, Qiang; Sun, Rui; Huang, Ying; Sun, Hao; Wei, Guohua; Wang, Jingjie; Ma, Xiaochun; Bai, Zongqing; Zuo, Guohua; Wang, Xiaopeng; Li, Wei; et al.
Abstract: Random pore model was employed to calculate the reaction kinetics parameters of SH bituminous coal and Shenmu semi-coke blended fuels under high-temperature entrained flow combustion, and the reaction kinetics parameters was modified by the intrinsic reaction Arrhenius curve obtained from low temperature thermogravimetric experiments. Then the combustion reaction rate and intrinsic reaction order at different blending ratios of semi-coke were determined. The reaction kinetics parameters and carbon conversion rate of blended fuels were investigated based on the pore structure of fuel, the effects of blending ratio of semi-coke, initial partial pressure of oxygen and reaction temperature. The reaction order decreases with the increasing of semi-coke blended ratio except 100% semi-coke combustion has higher reaction order approximately as char pure burning. The distribution of oxygen alone the radius of particle was also calculated in this study. In the low oxygen reduction zone, the blending ratio of semi-coke has little effect on the carbon conversion of blended fuel, and the blending effect is enhanced with the increasing of oxygen content. Carbon conversion rate decreases with the increasing of blending ratio and increases with reaction temperature.